The Multinational New Ventures on Corporate Performance Under the Work Environment and Innovation Behavior - Wang, Zheng; Zong, Ke; Jin, Kim Hyun (Frontiers in Psychology, 2022)
To cope with economic globalization and improve the competitiveness of transnational start-ups, the impact of the work environment and innovation behavior on corporate performance of multinational new ventures is analyzed. First, a model of the interaction among environment, innovation behavior, and enterprise performance is proposed. Then, 296 transnational start-ups in coastal areas are surveyed, and the model results are analyzed. Finally, a series of results are obtained. The results show that from the perspective of psychology, work dynamic organizational learning environment has a positive impact on enterprise performance (standardized path coefficient 0.436, P<0.01), and resource environment has a significant positive impact on enterprise performance (standardized path coefficient 0.425, P<0.01). Strategic environment also positively affects enterprise performance (standardized path coefficient 0.474, P<0.01). Therefore, the working environment of multinational new ventures has a positive impact on firm performance, and the mediating function between the working environment and firm performance is firm innovation behavior. With the research to achieve enterprise innovation of multinational new ventures by improving their response to the dynamic environment, the corporate performance has been greatly promoted, and finally the new ventures would participate in the international market competition.